Hambrick and Mason's "Upper Echelons Theory": evolution and open avenues. Issue 1 (26th October 2018) - Abatecola, Gianpaolo; Cristofaro, Matteo
Abstract : Purpose: How has upper echelons theory (UET) (Hambrick and Mason, 1984 ) been evolving over time? Through the historical discussion, this paper aims to provide an updated – and also innovative from some aspects – big picture on this famous approach to strategic management. In fact, after more than 30 years since its original conceptualization, the authors believe that the UE field is mature enough for a critical attempt to provide all those scholars and practitioners interested in strategic leadership with a comprehensive ground for future analyses, a ground which, to the authors' knowledge, is still missing. Design/methodology/approach: The authors mostly use a historical narrative to offer a critical account of the conceptual and methodological developments occurring under UE lenses over time. The authors believe that the historical approach can be particularly useful because it can help understand and explain why and how these developments have been conjectured and implemented. Findings: Two mainly intertwined insights emerge from our analysis: on the one hand, the developments subsequent to the seminal 1984 UE model have gradually, although constantly, reduced its strongly voluntarist assumptions on strategic leadership toward more moderated co-evolutionary lenses; on the other hand, the emerging psychological and cognitive moderators of UE variables are presently reinforcing the centrality of dominant coalitions, in that they affect their decision-making processes and strategic choices. Originality/value: From the critical discussion, a possible updated UE model based on co-evolutionary lenses finally emerges. Prospective research avenues in this management field are also provided.